Kearifan Lokal dan Ketaatan Adat: Studi Kualitatif tentang Kebudayaan dan Sistem Pemerintahan di Kampung Naga - Saptiani Indrawati; Mohamad Abduh; Agitsna Pradyta Maulidya; Siti Nurcholifia; Andi Maulana Sidik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Kampung Naga, a traditional village in Tasikmalaya renowned for its cultural authenticity and unique governance system, is the focus of this study. The research aims to delve deeper into the local wisdom and adherence to traditions among the Kampung Naga community. Using a qualitative approach, the study analyzes how traditional values and customary governance systems impact the daily lives of the Kampung Naga residents. The findings indicate that the Kampung Naga community continues to uphold inherited local wisdom, such as mutual cooperation, consensus-based decision-making, and respect for nature. Adherence to customs also serves as a strong foundation in preserving the cultural and social integrity of the community. The study concludes that local wisdom and adherence to customs play a crucial role in shaping the identity and sustainability of the Kampung Naga community.